Oral Health Literacy and Related Factors among Pregnant Women Referring to Health Government Institute in Kerman, Iran - Marzieh Karimi Afshar; Molook Torabi; Mahshid Bahremand; Mehrnaz Karimi Afshar; Fatemeh Najmi; Iman Mohammadzadeh (Association of Support to Oral Health Research (APESB), 2022)
Objective: To evaluate oral health literacy among pregnant women in Kerman, Iran. Material and Methods: The present cross-sectional study was conducted on 169 pregnant women referring  to government institute. Data were collected by demographic profile (including age, number of children, educational level, dental attendance before pregnancy and economic status), 17-item oral health literacy questionnaire consisting of four domains (including reading comprehension, numeracy, listening, and decision-making skills), self-assessment oral health status, DMFT index and oral health behavior. Data were analyzed by SPSS version 21 software using ANOVA and Chi-square tests at a significance level of 0.05. Results: The mean age of participants was 27.92 ± 5.25 years, 38.2% of them had bachelor's degree, 35.8% had dental attendance before pregnancy and 29.1% brushed daily their teeth twice or more. Dentists were the most frequent source of oral health information. Moreover, 60.0% believed their oral health was to be moderate, and 59.4% had inadequate oral health literacy. There was also  a  significant  correlation between educational level, monthly income and dental attendance before  pregnancy.  Conclusion: Our results showed inadequate oral health literacy among pregnant women, highlighting the necessity of dental consultation before pregnancy.